Nanoparticles in the air of the working zone as a risk factor for the health of workers of various industries - A. I. Sevalnev; L. P. Sharavara; A. V. Kutsak; O. O. Nefodov; O. A. Zemliynyi; K. I. Pisarevskyi; O. S. Shevchenko (Medičnì Perspektivi)
Purpose: analysis of scientific literature, summarizing data on domestic and foreign experience of assessing the determination of nanoparticles in the air of the working zone as a risk factor for the health of workers of various industries. The article analyzes the literature data on the study of the content of fine dust and nanoparticles in the atmospheric air and air of the working zone of different industries. Numerous studies indicate that fine dust is contained in the emissions of many industrial enterprises. According to the World Health Organization by level of impact on human health, suspended particles in the air and especially in the air of the working zone belong to the priority pollutants. Evaluation of the dust content in the air of large industrial cities is particularly relevant, because of a large number of sources of dust emissions of various origins in urban areas. Various technological processes contribute to the formation of fine dust and nanoparticles which pollute the ambient air and the air of the working zone. Data on the negative impact of fine dust and nanoparticles on health of workers are presented. Attention is paid to the problem of hygienic assessment of nanoscale dust content in the working zone air. The obtained results indicate that today the issues of studying the physicochemical properties of nanoparticles, their toxicity to the body, analysis of potential risks to humans, the development of an effective and reliable system for monitoring ultrafine particles in the environment and the production environment are still relevant as for informing employees about the risks involved, reducing and preventing harmful effects on humans. The potential negative effects on workers’ health determine the need and opportunity for further research in this area.